Pengaruh Model Pembelajaran Brain Writing Terhadap Kemampuan Menulis Cerita Pendek Peserta Didik Kelas XI SMK Negeri 4 Medan Tahun Ajaran 2023/2024 - Desi Monika Sagala; Frinawaty L Barus (FKIP, Universitas Palangka Raya, 2024)
This study aims to determine the effect of the brain writing learning model on the ability to write short stories in class XI students of SMK Negeri 4 Medan. The population of this research is all class XI as many as 286 people. This sample consisted of two classes of 58 students, class XI AV, control class (n = 28), experimental class (n = 28). This research method uses an experimental method with the type of post-test only control group design with a quantitative approach. This instrument is used with an essay test. The results of the study 1) the ability to write short stories in class XI AV3 students (control class) at SMK Negeri 4 Medan using the highest teacher centered learning (TCL) learning model is in the sufficient category with a percentage of 53% of 28 students. 2) the ability to write short stories in class XI AV1 (experimental class) SMK Negeri 4 Medan using the brain writing learning model is in the very good category 53% of 28 students. Thus it is said that the value of the ability to write short stories in the experimental class is higher than the control class. Based on the results of the analysis, the average post-test score for the control class was 61.46 with a standard deviation of 15.12; and the average score of the post-test scores for the experimental class was 84.6 with a standard deviation of 4.23. An increase of 23.14% occurred through the difference in post-test and post-test scores. The results of the calculation of the hypothesis test Tcount = 6.29 with t table at a significant level of 0.05 with df = n-1, df = 28-1 = 27 at a significant level α = 0.05 = 2.051. Because tcount > ttable, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. Based on the results of the analysis above, it can be concluded that there is an influence of the brain writing learning model on the ability to write short stories for class XI students of SMK Negeri 4 Medan in the 2023/2024 Academic Year.